Early Children's Language Development Through Storying Method - Fasiha Shah; Annizhofazul Fitria Najla Sembiring; Dina Khairiah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The development of early childhood language through the storytelling method in kindergarten is the development of children in acquiring words effectively orally and in writing. Its purpose as a means of communication, broaden horizons and knowledge. It helps children to interact well with their social environment. The storytelling method is one of the efforts in developing language development in early childhood. For this reason, the problem raised in this study is how the language development of children after an early age through the storytelling method is used, to answer the research problem, a qualitative research type with a descriptive approach is used. The research subjects were teachers and students, the data collection techniques were observation, interviews and documentation. The result of the research is that the development of the storytelling method has developed for early childhood language development. In the implementation of the teacher has been optimal in using the storytelling method. Qualitative data analysis is inductive, namely an analysis based on the data obtained, then developed.